Direct Electrical Stimulation of Premotor Areas: Different Effects on Hand Muscle Activity during Object Manipulation. (2nd September 2019) - Fornia, Luca; Rossi, Marco; Rabuffetti, Marco; Leonetti, Antonella; Puglisi, Guglielmo; Viganò, Luca; Simone, Luciano; Howells, Henrietta; Bellacicca, Andrea; Bello, Lorenzo; Cerri, Gabriella
Abstract: Dorsal and ventral premotor (dPM and vPM) areas are crucial in control of hand muscles during object manipulation, although their respective role in humans is still debated. In patients undergoing awake surgery for brain tumors, we studied the effect of direct electrical stimulation (DES) of the premotor cortex on the execution of a hand manipulation task (HMt). A quantitative analysis of the activity of extrinsic and intrinsic hand muscles recorded during and in absence of DES was performed. Results showed that DES applied to premotor areas significantly impaired HMt execution, affecting task-related muscle activity with specific features related to the stimulated area. Stimulation of dorsal vPM induced both a complete task arrest and clumsy task execution, characterized by general muscle suppression. Stimulation of ventrocaudal dPM evoked a complete task arrest mainly due to a dysfunctional recruitment of hand muscles engaged in task execution. These results suggest that vPM and dPM contribute differently to the control of hand muscles during object manipulation. Stimulation of both areas showed a significant impact on motor output, although the different effects suggest a stronger relationship of dPM with the corticomotoneuronal circuit promoting muscle recruitment and a role for vPM in supporting sensorimotor integration.